Pengaruh Social Context Mobile Marketing dan Brand Equity terhadap Motivasi Perjalanan Wisatawan - Yulia Hamdaini Putri; Dessy Yunita; Suhartini Karim (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2020)
In the era of digital information, many visitors get information on social media channels. The travelers or bloggers write their experiences in various places of their tours of the blog page or social media. Generally, this media would be a source of information about people that are interested traveling at any place. Tourist attractions place that has a lot of reviews of social media or web would increase it’s brand equity. A good brand equity would increase travelers' travelled motivation.Firstly, this study aims to identify and understand socomo marketing effects on Travel Motivation. Secondly, to identify and understand Brand Equity effects on Travel Motivation. The last, to identify and understand how brand equity acts as a moderating variable. This study using sampling with Slovin method. The required number of samples is four hundreds that had visited the marine tourism Palembang, Bedegung Waterfall Tourism, Gunung Dempo and Goa Putri.Sample selection using purposive sampling. We got data onto interview and questioners with seven scale likert. The technique used in this study is hypothesis testing using structural equation modeling technique. Firstly, SoCoMo Marketing has not an influence on travel motivation. The role of social media, reviews for attractions in a web and online map accuracy in pointing out places of tourist sites can increase a person's desire to visit it. Secondly, brand equity affects a person to visit a tourist place, the more famous tourist place name would make people feel confident to visit the place. Third, SoCoMo Marketing affects Brand Equity, the more good image and review information would increase the brand equity of tourist attractions thus would enhance tourist travelling.